THE ROLE OF SCIENTIFIC THINKING IN THE REALISTIC REFLECTION OF REALITY IS INTERPRETED BY YUSUF SHOMANSUR (TAMADDUN NURI JURNALI, 2025)
This article discusses the creative research of Yusuf Shomansur as a critic. It contains the author's views on the role of scientific thinking in realistic reflection of reality. Opinions are given about how Yusuf Shomansur interpreted the influence of scientific works on the works of Maqsud Sheikhza and Izzat Sultan.